The Students’ Perceptions of Using Augmented Reality as An Interactive Learning Media - Siti Nurjanah; Agung Dian Putra; Miranda Abung; Nindy Profithasari; Oktari Pradina Anggi (EBTIDA': Jurnal Pendidikan Dasar Islam, 2025)
The aims of this study to determine students’ perceptions of the use of Augmented Reality (AR) as an interactive learning medium. The research was conducted among 87 students of the 2023 cohort in the Primary School Teacher Education (PGSD) program. This research employed a quantitative method with a descriptive approach. The data were collected using a questionnaire distributed via Google Form, and analyzed using percentage-based descriptive analysis techniques. The results of the study indicate that students’ perceptions of the use of Augmented Reality as an interactive learning medium are categorized as good, with an average score of 3.12 on a 4-point scale, equivalent to 78%. These findings suggest that the use of AR can enhance students’ engagement, interest, and understanding of learning materials through a more interactive and contextual learning experience. Therefore, Augmented Reality can serve as an effective and innovative learning medium in higher education, particularly in improving the quality of technology-based learning within the Primary School Teacher Education program.